Catástrofe, trauma e dor - Lima, Suzana Maria da Silva Ferreira (2011)
This research reflects on the psychic trauma and the affectations that emerge from this experience in the clinic. For this purpose, it will be used Freudian theory of trauma as a random event whose quantum of pain cannot be assimilated by the ego, as well as the Ferenczian concept of autoclivagem as a psychic mechanism used by the ego as protection from trauma. The construction of metapsychology is guided by the position of fundamental psychopathology that prioritizes the research of the affectations raised in the act of clinic. The guiding case is about a woman whose hair was pulled by the motor shaft of a boat. This accident occurs in riverside areas along the Northern Brazil and is called scalping . It is a catastrophic accident characterized by partial or total loss of the scalp, becoming an event that causes turnaround in the person who experienced, producing significant changes in that person s life. In the course of this work, we turn to the clinic to name the position of the analyst before the pain. In this sense, we highlight the writings of Nasio (1997) to elucidate: tune yourself with the pain, try to vibrate with it, and, in this state of resonance, expect to spend time and words. (p. 17) Thus, it is essential to be able to wait for a time when the pain may have another sense. The analyst offers his body as a mediator between the self and the pain so he can also bear witness to the narrative of trauma and lead to a possible transformation of traumatic experience in experience